Хто в сім’ї голова, а хто шия? - Мацюк, Зоряна Сергіївна; Matsiuk, Zoriana S. (Волинський національний університет імені Лесі Українки, 2010)
У статті проаналізовано концептуалізацію “чоловіка” і “жінки” у фразеології Західного Полісся. Простежено спільність і відмінність у поведінці чоловіків і жінок у ритуальному житті досліджуваного регіону. I his article deals “wife” in phraseology of Western Polessia. Extensive attention has also been paid to the difference in the behavior of husbands and wives in ritual life of the inhabitants of the region which is under investigation.
Who is Real and Who is a Neck in the Family?
Keywords: концептосфера; гендер; чоловік; жінка; фразема; Західне Полісся; gender; husband; wife; phraseme; Western Polessia